Identity, Expression and Preferences of Muslim Youth Towards Da`Wah Content: Study on Podcasts at Islamic University of Bandung - Aldreka, Ridfiazhi; Muhtadi, Asep S.; Fardiah, Dedeh (Aqlam: Journal of Islam and Plurality, 2025)
Abstract: The rapid development of digital technology has transformed communication and information access, including Islamic propagation (da'wah). This study explores Universitas Islam Bandung (Unisba) students' preferences for digital da'wah content, particularly podcasts, using Berger and Luckmann's Social Construction of Reality theory and the bilisani qaumihi principle. Through qualitative methods, including in-depth interviews and observations targeting students aged 18-24, findings reveal preferences short, engaging, and visually appealing content for entertainment and long-form, educational content for deeper understanding. Platforms like TikTok, Instagram, and YouTube Shorts cater to short-form needs, while YouTube podcasts provide extensive and systematic discussions. Students favor relatable themes such as self-development, mental health, and daily Islamic practices, delivered in a relaxed, humorous, and relatable tone. The study concludes that digital da'wah must integrate entertainment with education to adapt to Generation Z's preferences, ensuring message relevance and effective Islamic value internalization in daily life.Key Words: Digital Da'wah, Student Preferences, Podcast, Social Media, Social ConstructionAbstrak: Perkembangan teknologi digital mengubah cara komunikasi dan akses informasi, termasuk dakwah Islam. Penelitian ini mengkaji preferensi mahasiswa Universitas Islam Bandung (Unisba) terhadap konten dakwah digital, khususnya podcast, dengan menggunakan teori Konstruksi Sosial atas Realitas dari Berger dan Luckmann serta prinsip bilisani qaumihi. Melalui metode kualitatif, termasuk wawancara mendalam dan observasi dengan target mahasiswa berusia 18-24 tahun, hasil penelitian menunjukkan preferensi konten singkat, menarik, dan visual untuk hiburan, serta konten panjang dan edukatif untuk pemahaman mendalam. Platform seperti TikTok, Instagram, dan YouTube Shorts memenuhi kebutuhan konten singkat, sementara podcast di YouTube memenuhi kebutuhan diskusi mendalam dan sistematis. Mahasiswa menyukai tema relevan seperti pengembangan diri, kesehatan mental, dan praktik Islami sehari-hari, dengan gaya penyampaian santai, humoris, dan relatable. Penelitian ini menyimpulkan bahwa dakwah digital harus mengintegrasikan hiburan dan pendidikan untuk beradaptasi dengan preferensi generasi Z, memastikan relevansi pesan, dan memungkinkan internalisasi nilai Islam dalam kehidupan sehari-hari.Kata Kunci: Dakwah Digital, Preferensi Mahasiswa, Podcast, Media Sosial, Konstruksi Sosial